2015
DOI: 10.5539/jas.v7n10p291
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Antimicrobial Properties of the Aqueous Ethanolic Extract of Saccharum officinarum (Sugarcane) Bark

Abstract: Phytochemical analysis and antimicrobial activities of the aqueous ethanolic extract of Saccharum officinarum were carried out. The antimicrobial activity was screened by disc diffusion method while the analysis of the different phytochemicals was carried out using standard methods. The result showed that the extract had inhibitory effects on the gram negative bacteria (Escherichia coli and Pseudomonas aeruginosa). The effect of the extract was minimal on Staphylococcus aureus, a gram positive bacteria suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
0
7
1
1
Order By: Relevance
“…This could be due to some feeding deterrents contained in the herb extracts such as saponins which are known to lower food palatability in decapod crustaceans (Chen, Chen, & Chen, ; Yeh, Liu, Sung, Lee, & Cheng, ). While sugarcanes contain a high level of saponins (Uchenna, Adaeze, & Steve, ; Williams, Onyenweaku, & Atangwho, ), the administration of pure SJ in the test feed did not cause a negative effect on the feeding of S. tranquebarica but accelerated their feed intake in the present study. This is probably due to a masking of saponins by sugars in the SJ.…”
Section: Introductioncontrasting
confidence: 51%
“…This could be due to some feeding deterrents contained in the herb extracts such as saponins which are known to lower food palatability in decapod crustaceans (Chen, Chen, & Chen, ; Yeh, Liu, Sung, Lee, & Cheng, ). While sugarcanes contain a high level of saponins (Uchenna, Adaeze, & Steve, ; Williams, Onyenweaku, & Atangwho, ), the administration of pure SJ in the test feed did not cause a negative effect on the feeding of S. tranquebarica but accelerated their feed intake in the present study. This is probably due to a masking of saponins by sugars in the SJ.…”
Section: Introductioncontrasting
confidence: 51%
“… Leaves, rind, stalks, roots, bagasse, molasses. Hussain et al [ 153 ]; Juttuporn et al [ 40 ]; Khaliq et al [ 130 ]; Shafiga-Atikah et al [ 154 ]; Uchenna et al [ 127 ]; Williams et al [ 155 ]; Zhao et al [ 42 ] Staphylococcus aureus Chlorogenic acid, ferulic acid, gallic acid, p-coumaric acid, phenylvaleric acid, quinic acid, sinapic acid, syringic acid, tannic acid, apigenin. Leaves, rind, stalks, bagasse, molasses.…”
Section: Functional Description Of Bioactive Compounds As Human Healt...mentioning
confidence: 99%
“…Several previous researchers reported that Saccharum officinarum L. has medicinal properties including antibacterial 26 and anti-cancer. 27 Phytochemical test results show that Saccharum officinarum L contains alkaloid compounds 28 , tannins 26,28 , saponins 26 , flavonoids 26 , also reducing sugars and anthracene glycosides 26 , carbohydrates 26,28 , protein 28 , and resin. 28 Studies that have been carried out on the Musa paradisiaca L plant, among others, show that banana flowers are reported to have anticancer properties 29 and banana leaves can be used to treat wounds.…”
Section: Resultsmentioning
confidence: 99%